Pengaruh Motivasi Dan Minat Berwirausaha Terhadap Memulai Usaha Baru Pada Mahasiswa (Fakultas Psikologi Universitas Sumatera Utara) - Siagian, Rizky Arrasyid; Siregar, Dahrul; Suryani, Wan (Mahesa Research Center, 2025)
The world of education is expected to have a big role in overcoming problems related to unemployment in Indonesia. The entrepreneurship course aims to foster students' tendency to open their own business (entrepreneurship) in the future. Many factors can influence students to become entrepreneurs in the future and the aim of this research is to analyze the influence of motivation and interest in entrepreneurship on opening a new business among students at the Faculty of Psychology, University of North Sumatra. This type of research is quantitative with an associative approach. The research population was students from the Faculty of Psychology, University of North Sumatra for the 2019 academic year, namely 242 people and 70 people using the Slovin formula were taken as the research sample. Data collection techniques through distributing questionnaires and documentation. The analysis technique used is multiple linear regression analysis and previously a classical assumption test was carried out. The results of the research show that motivation and interest in entrepreneurship have a partial or simultaneous influence on opening a new business among students at the Faculty of Psychology, University of North Sumatra.